Isolation of an Anti-Cancer Asperuloside from Hedyotis corymbosa L. - Nina Artanti; Muhammad Hanafi; Rina Andriyani; Vienna Saraswaty; Linar Zalinar Udin; Puspa D Lotulung; Ken Ichi Fujita; Yoshinosuke Usuki (Journal of Tropical Life Science, 2015)
Hedyotis corymbosa, with local name rumput mutiara, is an anti-inflammatory, anti-cancer and hepatoprotective traditional medicine.  The ethanol extract of H. corymbosa L. shows inhibitory activity to human YMB-1 breast cancer cell line with an IC50 of 6.51 mg/ml.  The methylene chloride fraction shows a potential cytotoxic activity with an IC50 of 2.75 mg/ml.  To obtain a lead compound, the extract was further purified by column chromatography. A pure compound is obtained which shows inhibitory activities against YMB-1, HL60 and KB human cell lines with IC50 values of 0.7; 11.0 and 104.2 mg/ml, respectively.  Based on the 1D and 2D FT-NMR data, the isolated compound is an asperuloside.